Jump Gait in Spastic Diplegia: An Expert Panel Case Review: Current Concept Review - Shrader, Wade; Shore, Benjamin; Scher, David; Kay, Robert (Journal of the Pediatric Orthopaedic Society of North America, 2021)
A detailed, thoughtful examination of a patient’s gait is an important aspect of the care of most patients in orthopaedics. Many times, an appropriate visual inspection of gait can reveal the most important pathologies seen in a general pediatric orthopaedic practice. However, some conditions, such as cerebral palsy (CP), often present with significant gait complexities and multiple impairments that negatively affect patient mobility. The use of advanced instrumented gait and motion analysis has become an essential piece of high-quality care of children with CP. In this edition, we discuss evaluation and management of jump-gait. In this series, a group of gait experts will be presenting principles and tips to help us all improve in the evaluation of gait in patients with CP. This case will include clinical information, physical examination data, pertinent radiographs, links to gait videos, and motion analysis data.